Epidemiological evolution of COVID-19 in Brazil and worldwide (Research, Society and Development, 2020)
Objective: to analyze the epidemiological evolution of COVID-19 in Brazil correlating to the current world scenario. Methodology: this is an analytical and documentary epidemiological study with a quantitative and descriptive approach of secondary data from COVID-19 of the Special Epidemiological Bulletin number 15 of the Ministry of Health of Brazil on the epidemiological situation until May 8, 2020. Results: the United States leads in number of confirmed cases 1,318,787 (33%) and deaths 78,503 (28%) in the world. Brazil, occupies the 8th place with 145,328 (4%) of the confirmed cases of COVID-19, its lethality is 6.8% and mortality is 46.6 per 1,000,000 inhabitants. In 2020, 107,895 hospitalizations for Severe Acute Respiratory Syndrome were registered in Brazil, of which 27,086 (25%) were confirmed cases of COVID-19 and 7,514 (28%) died, with people aged 60 or over 5,697 (69%) of the cases and heart diseases and diabetes were the risk groups that stood out considerably in the deaths of the elderly. Conclusion: the disease is not yet under control, social distance and the use of masks are the best way to prevent the progression of cases and deaths by COVID-19.